1980
DOI: 10.1007/bf00310441
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of cerebral high affinity receptor sites by lead and mercury compounds

Abstract: Abstract. The effect of various concentrations of several lead and mercury compounds upon various high affinity receptor sites within discrete brain regions has been measured. The specific binding of radioactive spiroperidol and quinuclidinyl benzilate to striatal and cortical membranes respectively, was much more severely inhibited in the presence of tri-n-butyl lead acetate than by lead acetate. This suggested that the hydrophobic organic lead derivative was able to interfere with receptor structure more rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The inhibition by triethyl Pb in the present experiments, in the presence of 0.3 to 1.0 nM [3H]QNB, was similar to that by tri-n-butyl lead reported by Bondy and Agrawal (13). The mechanisms of the inhibition by organolead are generally accepted to involve interactions with amino acid residues or SH gourp(s) within the allosteric binding sites of the receptor molecule (13).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The inhibition by triethyl Pb in the present experiments, in the presence of 0.3 to 1.0 nM [3H]QNB, was similar to that by tri-n-butyl lead reported by Bondy and Agrawal (13). The mechanisms of the inhibition by organolead are generally accepted to involve interactions with amino acid residues or SH gourp(s) within the allosteric binding sites of the receptor molecule (13).…”
Section: Resultssupporting
confidence: 89%
“…Bondy and Agrawal (13) reported that tri-nbutyl lead acetate inhibited the binding of [3H]QNB to membranes from rat brain in the presence of 1 nM QNB. The inhibition by triethyl Pb in the present experiments, in the presence of 0.3 to 1.0 nM [3H]QNB, was similar to that by tri-n-butyl lead reported by Bondy and Agrawal (13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A list of the possible plasma receptors is given in Table 9.3. The affinity of the dopamine receptor for dopamine has been shown to be decreased by lead and mercury (Bondy and Agrawal, 1980). The muscarinic cholinergic receptor that binds acetylcholine is easily separated and has been well characterized.…”
mentioning
confidence: 99%
“…, thiol groups of proteins, peptides and amino acids), interactions of mercury compounds with proteins in the CNS may explain some of their effects on neurotransmission. Mercury micromolar concentrations inhibited cholinergic, glutamatergic, GABAergic and dopaminergic systems [ 47 , 48 , 49 , 50 , 51 ], affecting both behavior and cognition. It is well established that cognitive and motivational processes depend on the connections between PFC and limbic structures, which are dependent on the neurotransmitters cited above, and the hippocampus plays a key role in the functioning of these pathways [ 43 ].…”
Section: Discussionmentioning
confidence: 99%